Simulation of fluid sloshing in a tank using the SPH and Pendulum methods - Vidmar, Vesna (Acta hydrotechnica, 2018)
We simulated liquid sloshing in a circular road tanker during two typical manoeuvres, namely steady-turn and lane change. A quasi-static pendulum, a modified dynamic pendulum with adjustable rod length, and the SPH (Smooth Particle Hydrodynamics) model Tis Isat were applied to simulate liquid oscillations. A simplified vehicle-tanker overturning model was developed and applied in order to determine the overturning threshold for the first manoeuvre. The agreement of liquid oscillations between the applied methods was better in the second manoeuvre, while the maximum inclination of the liquid gravity centre was successfully simulated in both cases. Both dynamic methods, the SPH and the dynamic pendulum, show a significantly lower overturning threshold, while all methods show similar overturning behaviour for a vehicle with liquid cargo. The threshold computed using the SPH model is slightly higher than with the dynamic pendulum due to wall-particle and particle-particle interactions. The results and comparisons confirm the suitability of the SPH method for simulating sloshing in road tankers and also show the method%s advantages: realistic description of the non-linear free surface in real-time, along with a consideration of mixing and friction processes within the fluid.
Keywords: closed domain; fluid oscillations; liquid cargo; metoda SPH; nihalo; nihanje kapljevine; overturning threshold; pendulum; prag prevrnitve; SPH method; tekoči tovor; zaprto območje